2017
DOI: 10.3389/fncel.2017.00176
|View full text |Cite
|
Sign up to set email alerts
|

Cell Polarity in Cerebral Cortex Development—Cellular Architecture Shaped by Biochemical Networks

Abstract: The human cerebral cortex is the seat of our cognitive abilities and composed of an extraordinary number of neurons, organized in six distinct layers. The establishment of specific morphological and physiological features in individual neurons needs to be regulated with high precision. Impairments in the sequential developmental programs instructing corticogenesis lead to alterations in the cortical cytoarchitecture which is thought to represent the major underlying cause for several neurological disorders inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 195 publications
(281 reference statements)
0
48
0
Order By: Relevance
“…We observed that the levels of filamentous (F) actin in primary dissociated cells, as indicated by phalloidin-rhodamine abundance, significantly decreased after mTOR inhibition or hyperactivation ( Figure 4A; n>7 cells/group from three independent experiments). The Rho GTPases, RHOA, RAC1 and CDC42, are actin regulators and prime candidate molecules to affect radial glial morphology and migration as Rho-ROCK signaling is required for oRG MST divisions (Hansen et al, 2017;Ostrem et al, 2014b) and CDC42 maintains radial glial polarity during mouse cortex development (Yokota et al, 2010). Dissociated primary oRG cells express CDC42, which decreases after treatment with rapamycin or BDNF, suggesting that optimal mTOR signaling maintains total CDC42 levels ( Figure 4C; n>3 cells/group from five independent experiments).…”
Section: Radial Fiber Truncation Following Mtor Dysregulation Is Rescmentioning
confidence: 99%
“…We observed that the levels of filamentous (F) actin in primary dissociated cells, as indicated by phalloidin-rhodamine abundance, significantly decreased after mTOR inhibition or hyperactivation ( Figure 4A; n>7 cells/group from three independent experiments). The Rho GTPases, RHOA, RAC1 and CDC42, are actin regulators and prime candidate molecules to affect radial glial morphology and migration as Rho-ROCK signaling is required for oRG MST divisions (Hansen et al, 2017;Ostrem et al, 2014b) and CDC42 maintains radial glial polarity during mouse cortex development (Yokota et al, 2010). Dissociated primary oRG cells express CDC42, which decreases after treatment with rapamycin or BDNF, suggesting that optimal mTOR signaling maintains total CDC42 levels ( Figure 4C; n>3 cells/group from five independent experiments).…”
Section: Radial Fiber Truncation Following Mtor Dysregulation Is Rescmentioning
confidence: 99%
“…Through consecutive waves of neurogenesis, nascent neurons migrate radially along the RGP cell process into the most superficial layer of the developing cortex where they mature and differentiate. This process continues with each new wave of neurons migrating past the previous, resulting in the formation of distinct cortical laminae in an ‘inside‐out’ fashion . Early born, deep layer neurons (layers 5–6) are largely composed of corticofugal neurons that innervate brain regions beyond the neocortex including the thalamus, brainstem, and spinal cord .…”
Section: Radial Glia Progenitors Generating Cell Type Diversity In Thmentioning
confidence: 99%
“…We begin, however, with a brief summary of the key features of cortical development. For more in-depth reviews on this topic see Paridaen and Huttner (2014), Taverna et al (2014), Lodato and Arlotta (2015), Hansen et al (2017), and Huttner and Wieland (2019).…”
Section: Introductionmentioning
confidence: 99%